MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DI MADRASAH TSANAWIYAH AL-ISHLAH DANAU PAUH KABUBATEN MERANGIN PROVINSI JAMBI - Yusria; Zillimin; Aci Purnamasari; Mahfuzah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Educational facilities and infrastructure are important components in education and are one of the eight National Education Standards. The purpose of this study was to determine the process of educational facilities and infrastructure at Al Ishlah Islamic Boarding School, to determine the obstacles to the implementation of educational facilities and infrastructure at Al Ishlah Islamic Boarding School and to determine solutions to improve Facilities and Infrastructure at Al-ishlah Islamic Boarding School. The research method used by the researcher is a qualitative qualitative method. Research method approach Qualitative research is a descriptive and analytical research. Descriptive in qualitative research means describing and explaining events, phenomena and social situations being studied. The Head of the Boarding School and the Deputy Head of Infrastructure, are seen actively improving the learning process through several strategic steps, first by holding routine training. Second, by making periodic improvements to educational facilities and infrastructure, Third, by developing a relevant and responsive curriculum, and finally by conducting periodic evaluation and supervision of all aspects. This research is expected to achieve educational goals with supervision and evaluation in the management of educational facilities and infrastructure.